Optomechanical frequency comb induced by thermal and optical forces in NEMS-based cavity optomechanics - Xinchen Wan; Ji Xia; Haoyang Sun; Qingze Guan; Guangya Zhou (Communications Physics)
Abstract Frequency combs (FCs) have proven to be efficient tools in fields such as ranging, communication, and computing. Traditionally, these combs have a large footprint and require external devices for operation which limits their practicality in miniaturized systems such as on-chip photonic computing devices. To address these limitations, we propose an alternative method to generate FCs directly on a single chip, significantly reducing both the system footprint and power consumption. This approach leverages the natural interactions between thermo-optical effects and mechanical vibration. By leveraging a combination of thermo-optical effects and nonlinearity-induced frequency mixing within a single cavity system, we are able to generate stable frequency combs at room temperature without the need for external driving forces. Our experimental results confirm the theory, showcasing a potential pathway to more efficient and compact devices for communication and computation applications.